Current Trends in Caucasian, East European, and Inner Asian Linguistics : Papers in Honor of Howard I. Aronson - Aronson, Howard I. (Howard Isaac), 1936-; Holisky, Dee Ann; Tuite, Kevin (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2003)
This volume is a collection of seventeen papers, on languages of all three indigenous Caucasian families as well as other languages spoken in the territory of the former Soviet Union. Several papers are concerned with diachronic questions, either within individual families, or at deeper time depths. Some authors utilize their field data to address problems of general linguistic interest, such as reflexivization. A number of papers look at the evidence for contact-induced change in multilingual areas. Some of the most exciting contributions to the collection represent significant advances in the reconstruction of the prehistory of such understudied language families as Northeast Caucasian, Tungusic and the baffling isolate Ket. This book will be of interest not only to specialists in the indigenous languages of the former USSR, but also to historical and synchronic linguists seeking to familiarize themselves with the fascinating, typologically diverse languages from the interior of the Eurasian continent. Dee Ann Holisky is Professor of English and Linguistics, and Associate Dean for Academic Programs of the College of Arts & Sciences at George Mason University. She is the author of Aspect and Georgian Medial Verbs (Caravan Books, 1981) and of numerous articles on Georgian and Kartvelian linguistics. Kevin Tuite is Professor of Anthropology at the Université de Montréal. Among his books are An Anthology of Georgian Folk Poetry (Fairleigh Dickinson University Press, 1994) and Ethnolinguistics and Anthropological Theory (co-edited with Christine Jourdan; Montréal: Éditions Fides, 2003).